Diaphanous-related formin subfamily: Novel prognostic biomarkers and tumor microenvironment regulators for pancreatic adenocarcinoma - Zhang, Bixi; Hu, Qing; Li, Yanchun; Xu, Canxia; Xie, Xiaoran; Liu, Peng; Xu, Meihua; Gong, Siming; Wu, Hao (Frontiers in Molecular Biosciences, 2022)
The diaphanous-related formin subfamily includes diaphanous homolog 1 (DIAPH1), DIAPH2, and DIAPH3. DIAPHs play a role in the regulation of actin nucleation and polymerization and in microtubule stability. DIAPH3 also regulates the assembly and bipolarity of mitotic spindles. Accumulating evidence has shown that DIAPHs are anomalously regulated during malignancy. In this study, we reviewed The Cancer Genome Atlas database and found that DIAPHs are abundantly expressed in pancreatic adenocarcinoma (PAAD). Furthermore, we analyzed the gene alteration profiles, protein expression, prognosis, and immune reactivity of DIAPHs in PAAD using data from several well-established databases. In addition, we conducted gene set enrichment analysis to investigate the potential mechanisms underlying the roles of DIAPHs in the carcinogenesis of PAAD. Finally, we performed the experimental validation of DIAPHs expression in several pancreatic cancer cell lines and tissues of patients. This study demonstrated significant correlations between DIAPHs expression and clinical prognosis, oncogenic signature gene sets, T helper 2 cell infiltration, plasmacytoid dendritic cell infiltration, myeloid-derived suppressor cell infiltration, ImmunoScore, and immune checkpoints in PAAD. These data may provide important information regarding the role and mechanisms of DIAPHs in tumorigenesis and PAAD immunotherapy.